(untitled) (Texas Journal of Medical Science, 2024)
The article is devoted to a discussion of the most important aspects of studying the quality of life in children as an independent approach to assessing child health at the present stage. The work examines the main features of the methodology for assessing the quality of life of a child, presents the areas of children’s healthcare in which the use of the method of assessing the quality of life in children is the most popular and promising today and in the near future